One‐Pot Sequential Propargylation/Cycloisomerization: A Facile [4+2]‐Benzannulation Approach to Carbazoles. Issue 7 (14th January 2016) - Raji Reddy, Chada; Rani Valleti, Reddi; Dilipkumar, Uredi
Abstract: A novel one‐pot [4+2]‐benzannulation approach to substituted carbazoles is accomplished by acid‐catalyzed C3‐propargylation of 2‐alkenyl/aryl indoles with 1‐aryl propargylic alcohols, followed by cycloisomerization. A variety of 2‐alkenylated indoles and 2‐aryl/heteroaryl indoles successfully participated in this tandem reaction with 1‐aryl/heteroaryl propargylic alcohols to provide diversely substituted and annulated carbazoles, as well as an aza[5]helicene. Abstract : Six equals four plus two : A [4+2] benzannulation has been developed for the synthesis of diversely substituted and annulated carbazoles from 2‐alkenyl/aryl/heteroaryl indoles as C4 synthons and 1‐aryl propargylic alcohols as C2 synthons by following a one‐pot propargylation/cycloisomerization reaction sequence (see scheme; Boc= tert ‐butoxycarbonyl; DBU=1, 8‐diazabicyclo[5.4.0]undec‐7‐ene).